Incubator successes: Lessons learned from successful incubators towards the twenty-first century. Issue 1 (1st April 2014) - Mubarak AL-Mubaraki, Hanadi; Busler, Michael
Abstract : Purpose: – The purpose of this paper is twofold: first, discuss and analyse the successful adoption of incubators worldwide; and second, the lessons learned from successful incubators towards the twenty-first century. Design/methodology/approach: – The research methodologies adopted in this study are a mixed-methods approach: quantitative (survey) and qualitative (five international case studies). Findings: – Incubators contribute to the international economy and play a vital role not only in the economic recovery but also in smart growth and economic development. These findings will assist incubator managers, policy makers and government parties in successful implementation of incubator policies. Research limitations/implications: – This research focuses on specific lessons. More in-depth research may find additional positive traits. Practical implications: – This research will be of benefit to countries establishing business incubators in order to avoid mistakes and increase the likelihood of success. Originality/value: – This paper contributes to the current literate on the best practices worldwide. Furthermore, it presents future perspectives for academicians and practitioners.